2003
DOI: 10.1097/01.asn.0000094083.82845.fa
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Renal Secretion of Substrates for the Multidrug Resistance Protein 2 in Mutant Transport–Deficient (TR−) Rats

Abstract: Abstract. Previous studies with mutant transport-deficient rats (TR Ϫ ), in which the multidrug resistance protein 2 (Mrp2) is lacking, have emphasized the importance of this transport protein in the biliary excretion of a wide variety of glutathione conjugates, glucuronides, and other organic anions. Mrp2 is also present in the luminal membrane of proximal tubule cells of the kidney, but little information is available on its role in the renal excretion of xenobiotics. The authors compared renal transport of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 31 publications
(27 reference statements)
1
35
0
Order By: Relevance
“…Low expression or absence of MRP2 causes conjugated hyperbilirubinemia and pigment disposition in the liver, as observed in patients with the autosomal recessively inherited Dubin-Johnson syndrome, partly due to an impaired canalicular secretion of glutathione, glutathione conjugates, and bilirubin glucuronides (Paulusma et al, 1997;Smitherman et al, 2004). We found previously that the renal excretion capacity for a number of known Mrp2 substrates was decreased as well in an Mrp2-deficient rat (Masereeuw et al, 2003).…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Low expression or absence of MRP2 causes conjugated hyperbilirubinemia and pigment disposition in the liver, as observed in patients with the autosomal recessively inherited Dubin-Johnson syndrome, partly due to an impaired canalicular secretion of glutathione, glutathione conjugates, and bilirubin glucuronides (Paulusma et al, 1997;Smitherman et al, 2004). We found previously that the renal excretion capacity for a number of known Mrp2 substrates was decreased as well in an Mrp2-deficient rat (Masereeuw et al, 2003).…”
mentioning
confidence: 76%
“…These injections took place under anesthesia via a nose cone (5% isoflurane; Isoflo, Abbott Laboratories, Abbott Park, IL). Subsequently, rat kidneys were isolated and perfused as described in detail previously (Masereeuw et al, 2003). Based on the findings in our previous study, calcein-AM was used as a source for the fluorescent substrate calcein.…”
Section: Methodsmentioning
confidence: 99%
“…However, renal function seems unimpaired in TR Ϫ rats, which may be explained by a relatively minor role for Mrp2 in renal physiology as a result of the presence of various other compensatory organic anion transporters. On the other hand, we recently found that renal excretion of certain exogenous bulky organic anions in TR Ϫ kidney is either reduced (calcein, fluo-3) or delayed (lucifer yellow) (26). Furthermore, under the influence of drug treatment, MRP2 function may be altered.…”
Section: Discussionmentioning
confidence: 99%
“…Rat kidneys of Wistar-Hannover (WH) and TR Ϫ rats were isolated and perfused as described in detail previously (25,26). Research was undertaken under the auspices of a protocol approved by the local university animal care and usage committee.…”
Section: Kidney Isolation and Perfusionmentioning
confidence: 99%
“…Both transporters accept a variety of organic anions as substrates, such as p-aminohippurate (PAH), 17␤-estradiol-17␤-d-glucuronide, dehydroepiandrosterone sulfate (DHEAS), and methotrexate (18,(25)(26)(27). van Aubel et al (18) initially found that Mrp4 is localized on the BBM, and, subsequently, Mrp4 was suggested to play important roles in tubular secretion (18,25,28), although direct evidence of this still is lacking. For BCRP, an in vivo study using Bcrp knockout mice has demonstrated that BCRP is responsible for the urinary excretion of some organic anions, such as methotrexate and 6-hydroxy-5,7-dimethyl-2-methylamino-4-(3-pyridylmethyl) benzothiazole (E3040) sulfate (29,30).…”
mentioning
confidence: 99%